Regresi Logistik Ordinal untuk Memodelkan Predikat Lulusan Perguruan Tingggi - Fathurahman, M.; Orvanita; Darnah (LPPM Universitas Negeri Jakarta, 2023)
Logistic regression is an alternative model that can model the relationship between a categorical response variable and one or more categorical, continuous predictor variables, or a combination of categorical and continuous predictor variables. Based on the number of categories in the response variable, the logistic regression model consists of a dichotomous logistic regression model and a polychotomous regression model. The dichotomous logistic regression model is a logistic regression model that has two categories in the response variable and has a Bernoulli distribution. In comparison, the polychotomous logistic regression model is a logistic regression model that has three or more categories and a multinomial distribution. The polychotomous logistic regression model is divided into two models, namely the multinomial logistic regression model and ordinal logistic regression. This research aims to examine ordinal logistic regression modeling and its application to the predicate of graduates of the undergraduate program at the Faculty of Mathematics and Natural Sciences, Mulawarman University (FMIPA UNMUL) for the 2020 graduation period. The results of the research show that the factors that have a significant influence on the predicate of graduates of the FMIPA UNMUL undergraduate program are gender and admission route. Female graduates of the FMIPA UNMUL undergraduate program have a greater chance of achieving satisfactory and very satisfactory predicates compared to achieving a cum laude predicate. Graduates of the FMIPA UNMUL undergraduate program who are accepted through the SMMPTN admission route have a lower chance of achieving satisfactory and very satisfactory predicates compared to achieving a cum laude predicate.